The influence of relational experience and contractual governance on the negotiation strategy in buyer–supplier disputes - Lumineau, Fabrice; Henderson, James E. (Journal of Operations Management, 2012)
AbstractThis paper theoretically refines and empirically extends the debate on the type of interplay between relational experience and contractual governance in an under‐researched area: supply chain disputes. We define relational experience as either cooperative or competitive; distinguish between control and coordination functions of contractual governance; and assess their interplay on the negotiation strategy used in disputes. Using a unique data set of buyer–supplier disputes, we find, in particular that increasing contractual control governance weakens the positive effect of cooperative relational experience on cooperative negotiation strategy. However, increasing contractual control governance for a buyer–supplier dyad with competitive relational experience will increase cooperative negotiation strategy. Contractual coordination governance reinforces the positive effect of cooperative relational experience. Through this study, we reach a better understanding ofhowandwhencontractual and relational governance dimensions interact; rather thanwhetherthey act as substitutes or complements as has been studied in prior research. We discuss the implications of these findings for the field of supply chain management.